The role of Social Media Marketing in increasing Brand Awareness, Brand Image and Purchase Intention - Aekram Faisal; Iwan Ekawanto (Universitas Trisakti, 2021)
In recent years, social media is not only used for social interaction activities, but is also used as a medium for doing business. Especially at this time when the whole world is facing the covid 19 pandemic, where most countries make decisions about closing and restricting several physical places, which have been used to carry out business activities, entrepreneurs are trying to optimize digital media and social media as a strategy to market their products. This study aims to determine the role of social media marketing in increasing brand awareness, brand image and purchase intention. The design of this research is hypothesis testing. The study uses the Structural Equation Modeling (SEM) method with a sample of 331 respondents who are active users of social media in Indonesia, for at least 2 years and have purchased products marketed on social media. The results show that social media marketing activities based on entertainment, interaction, trendiness, customization, and word-of-mouth have a positive influence on brand awareness, brand image, and purchase intention. Furthermore, brand awareness has a positive influence in mediating social media marketing activities on purchase intentions, and brand image also has a positive influence in mediating social media marketing activities on purchase intentions. Thus, so that consumer intentions to buy products can increase, online shop owners can increase awareness and positive image of the brand, and to increase brand awareness and positive image of the brand, online shop owners can increase their marketing activities through social media.Keywords: Â Social Media Marketing, Brand Awareness, Brand Image, Purchase Intention.